Low‐fat/high‐fibre diet prehabilitation improves anastomotic healing via the microbiome: an experimental model. Issue 6 (26th December 2019) - Hyoju, S. K.; Adriaansens, C.; Wienholts, K.; Sharma, A.; Keskey, R.; Arnold, W.; van Dalen, D.; Gottel, N.; Hyman, N.; Zaborin, A.; Gilbert, J.; van Goor, H.; et al.
Abstract : Background: Both obesity and the presence of collagenolytic bacterial strains ( Enterococcus faecalis ) can increase the risk of anastomotic leak. The aim of this study was to determine whether mice chronically fed a high‐fat Western‐type diet (WD) develop anastomotic leak in association with altered microbiota, and whether this can be mitigated by a short course of standard chow diet (SD; low fat/high fibre) before surgery. Methods: Male C57BL/6 mice were assigned to either SD or an obesogenic WD for 6 weeks followed by preoperative antibiotics and colonic anastomosis. Microbiota were analysed longitudinally after operation and correlated with healing using an established anastomotic healing score. In reiterative experiments, mice fed a WD for 6 weeks were exposed to a SD for 2, 4 and 6 days before colonic surgery, and anastomotic healing and colonic microbiota analysed. Results: Compared with SD‐fed mice, WD‐fed mice demonstrated an increased risk of anastomotic leak, with a bloom in the abundance of Enterococcus in lumen and expelled stool (65–90 per cent for WD versus 4–15 per cent for SD; P = 0·010 for lumen, P = 0·013 for stool). Microbiota of SD‐fed mice, but not those fed WD, were restored to their preoperative composition after surgery. Anastomotic healing was significantly improved when WD‐fed mice were exposed to a SD diet for 2 days before antibiotics and surgery ( P < 0·001). Conclusion: The adverse effects of chronic feeding of a WD on the microbiota and anastomotic healing can be prevented by a short course of SD in mice. Surgical relevance Worldwide, enhanced recovery programmes have developed into standards of care that reduce major complications after surgery, such as surgical‐site infections and anastomotic leak. A complementary effort termed prehabilitation includes preoperative approaches such as smoking cessation, exercise and dietary modification. This study investigated whether a short course of dietary prehabilitation in the form of a low‐fat/high‐fibre composition can reverse the adverse effect of a high‐fat Western‐type diet on anastomotic healing in mice. Intake of a Western‐type diet had a major adverse effect on both the intestinal microbiome and anastomotic healing following colonic anastomosis in mice. This could be reversed when mice received a low‐fat/high‐fibre diet before operation. Taken together, these data suggest that dietary modifications before major surgery can improve surgical outcomes via their effects on the intestinal microbiome. Abstract : Mice fed a high‐fat/low‐fibre Western diet develop changes in their intestinal microbiota that are associated with an increase in the incidence of anastomotic leak. These changes persist for up to 1 month after operation in multiple compartments including expelled stool, luminal contents and within intestinal tissue, and are characterized by loss of the health‐promoting Bacteroidetes and an increase in collagenolytic Enterococcus, a pathobiont demonstrated previously to be linked causally to anastomotic leak. Strikingly, allowing mice to feed on a standard low‐fat/high‐fibre chow diet for only 2 days before operation resulted in a dramatic decrease in the anastomotic leak rate of mice chronically fed a high‐fat/low‐fibre Western diet associated with partial restoration of the microbiota. Reverses ill effects of western diet Abstract : Antecedentes: Tanto la obesidad como la presencia de cepas bacterianas colagenolíticas ( Enterococcus faecalis ) pueden aumentar el riesgo de fuga anastomótica. El objetivo de este estudio fue determinar si los ratones alimentados durante un tiempo prolongado con una dieta de tipo occidental con alto contenido en grasas ( western type diet, WD) desarrollaban una fuga anastomótica en asociación con una microbiota alterada, así como determinar si una dieta estándar preoperatoria de corta duración baja en grasa/alta en fibra ( standard diet, SD) podía mitigar la aparición de fuga. Métodos: Ratones machos C57BL/6 obtenidos de Charles River fueron asignados aleatoriamente a una dieta chow estándar (SD) o a una dieta de tipo occidental obesogénica (WD) durante 6 semanas, seguida de la administración preoperatoria de antibióticos y la realización de una anastomosis en el colon. La microbiota se analizó longitudinalmente después de la operación y se correlacionó con la curación utilizando una puntuación de cicatrización anastomótica ya establecida. En experimentos repetidos, los ratones con una WD durante 6 semanas fueron expuestos a una SD durante 2, 4 y 6 días antes de la cirugía de colon, analizándose la cicatrización de la anastomosis y la microbiota del colon. Resultados: Los ratones alimentados con WD en comparación con los alimentados con SD presentaron un mayor riesgo de fuga anastomótica con un rápido incremento en la abundancia de Enterococcus (65‐90% para WD versus 4‐15% para SD, P < 0, 01). La microbiota de ratones alimentados con SD, pero no con WD, se restableció a su composición preoperatoria después de la operación. La cicatrización anastomótica mejoró significativamente cuando los ratones alimentados con WD fueron expuestos a una dieta SD durante 2 días antes del tratamiento antibiótico y de la cirugía ( P < 0, 01). Conclusión: En ratones, los efectos adversos de una alimentación crónica con una WD sobre la microbiota y la cicatrización anastomótica se pueden prevenir mediante una SD de corta duración.